(untitled) (Journal of Partial Differential Equations, 1995)
Painlevé analysis is applied to analytic solutions of Noyes-Field system for Belousov-Zhabotinskii reaction. Some explicit travelling wave solutions are presented. The technique in this paper is also useful for other systems of nonlinear partial differential equations which may be integrable or non integrable.